Results of improvement of the reducer crane mechanisms - Y. V. Remizovich (Вестник СибАДИ, 2017)
In this article the reducer design with variable transfer number is offered and proved. The reducer allows to make dispersal and the movement of the crane (cart) with three speeds with smooth gear shifting. Couplings are built in cogwheels. Design compact, simple and reliable. Decrease in dynamic loadings, rocking of freight is provided. As a prototype couplings accepted way clutch cylindrical roller. The proposed clutch gearbox comprise tapered rollers. Keywords: reducer, coupling, transfer, speed.